Gendered Pasts: Historical Essays in Feminity and Masculinity in Canada - McPherson, Kathryn; Morgan, Cecilia; Forestell, Nancy M. (Canadian social history series, 2015)
It is commonplace today to suggest that gender is socially constructed, that the roles women and men fulfill in their daily lives have been created and defined for them by society and social institutions. But how have men and women negotiated and navigated the gender roles that have been thrust upon them? With Gendered Pasts, Kathryn McPherson, Cecilia Morgan, and Nancy M. Forestell have collected eleven engaging essays that seek to answer this question in a wide-ranging exploration of specific gendered dimensions of nineteenth- and twentieth-century Canadian history.The contributors cover all manner of topics related to gender and history across Canada, including: female vagrancy; gambling, drinking, and sex; the role of the miner's wife; the portrayal of gay men; and the sharply defined role of nurses. Unusual in its breadth, Gendered Pasts is essential to the understanding of the various threads and themes in Canadian gender history. Previously published by Oxford University Press, . --Publisher's description
Keywords: Sex role -- Canada -- History -- 19th century